Difference in Serum Levels of Vitamin D Between Canalolithiasis and Cupulolithiasis of the Horizontal Semicircular Canal in Benign Paroxysmal Positional Vertigo - Nakada, Takafumi; Sugiura, Saiko; Uchida, Yasue; Suzuki, Hirokazu; Teranishi, Masaaki; Sone, Michihiko (Frontiers in Neurology, 2019)
Background and purpose: In the horizontal canal benign paroxysmal positional vertigo (BPPV), canalolithiasis and cupulolithiasis show symmetrical, geotropic, and apogeotropic, nystagmus. The difference between canalolithiasis and cupulolithiasis is widely accepted to be the attachment of the displaced otoconia to the cupula of a semicircular canal; however, the factors affecting such attachment are unclear. Several studies have shown a relationship between BPPV and vitamin D deficiency, but no studies have compared serum levels of vitamin D between canalolithiasis and cupulolithiasis patients. The purpose of this study was to clarify the difference in vitamin D serum level between canalolithiasis and cupulolithiasis of the horizontal canal. Methods: This retrospective study included 20 and 15 patients with canalolithiasis and cupulolithiasis of the horizontal canal, respectively. Serum levels of 25-hydroxyvitamin D (25(OH)D) during the acute phase of BPPV were measured. Results: The mean 25(OH)D serum level in patients with canalolithiasis and cupulolithiasis was 13.2±1.4 and 20.4±1.6 ng/mL, respectively, and the difference was statistically significant (p = 0.0014), also after adjusting for age and sex (p = 0.0351). Eighteen out of 20 (90%) and 5 of 15 (33%) patients were diagnosed with vitamin D deficiency in the canalolithiasis and cupulolithiasis groups, respectively, and this difference was also statistically significant (p = 0.0005). Conclusion: We found that serum vitamin D level in patients with canalolithiasis was significantly lower than that in patients with cupulolithiasis of the horizontal canal. Vitamin D serum levels could differentiate between canalolithiasis and cupulolithiasis.